2014
DOI: 10.1002/2013ja019637
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the IMF cone angle control of Pc3‐4 pulsations observed on the ground

Abstract: Many studies have shown that Pc3-4 pulsations (~0.014-0.1 Hz) observed in Earth's magnetosphere during daytime hours originate in the ion foreshock region of the solar wind, just upstream from Earth's bow shock. They occur when the interplanetary magnetic field (IMF) is primarily radial-when the IMF cone angle θ xB ≤ 45°. However, our knowledge of ion foreshock conditions is often incomplete because of the very limited number of spacecraft providing upstream data. In this study we compared 13 months of wave ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 45 publications
1
31
0
Order By: Relevance
“…The three upstream parameters are all influential in the excitation and downstream propagation of ULF waves in the region upstream of the bow shock and their importance to the NN model suggests that UWs are the dominant drivers of mid-latitude dayside Pc3 waves on the ground. This is in agreement with previous studies by Yumoto (1985), Verő (1980), Bier et al (2014), Heilig et al (2007) and Heilig et al (2010), for example. Other extra-magnetospheric input parameters, such as the F10.7 flux, may be included in future models.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The three upstream parameters are all influential in the excitation and downstream propagation of ULF waves in the region upstream of the bow shock and their importance to the NN model suggests that UWs are the dominant drivers of mid-latitude dayside Pc3 waves on the ground. This is in agreement with previous studies by Yumoto (1985), Verő (1980), Bier et al (2014), Heilig et al (2007) and Heilig et al (2010), for example. Other extra-magnetospheric input parameters, such as the F10.7 flux, may be included in future models.…”
Section: Discussionsupporting
confidence: 94%
“…1 h). Furthermore, Bier et al (2014) showed that the cone angle values derived from OMNI may be inaccurate -especially when the IMF is oriented approximately parallel to the Sun-Earth line, when high Pc3 wave activity is expected. Table 3).…”
Section: Comparison Between High-resolution and Low-resolution Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, while Wolfe et al [] and Yumoto et al [] concluded for the absence of any control of the IMF direction on the (broadband) Pc3 amplitude at λ ≈ −74°, Ponomarenko et al [] determined, at the same latitude, a power maximum at θ XB ≈ 20° (narrowband events). On the other hand, a recent statistical study of the wave activity at two widely separated stations ( λ ≈ 74° and λ ≈ −62° [ Bier et al , ]) showed that the Pc3/4 power was associated with θ XB < 45°, ≈81% of the time. At lower latitudes ( λ ≈ 59°), Greenstadt et al [] determined active Pc3 intervals for θ XB < 50°; by contrast, Wolfe and Meloni [] found, at λ ≈ 56°, a very weak correspondence between the cone angle and the Pc3 power.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the OMNI data set in characterizing conditions near the nose of Earth's bow shock under predominantly radial IMF is not better than 80 % (Bier et al 2014).…”
Section: Introductionmentioning
confidence: 93%